2021
DOI: 10.3389/fonc.2021.748610
|View full text |Cite
|
Sign up to set email alerts
|

Large Granular Lymphocyte Expansion in Myeloid Diseases and Bone Marrow Failure Syndromes: Whoever Seeks Finds

Abstract: Large granular lymphocytes (LGL) are lymphoid cells characterized by either a T-cell or a natural killer phenotype whose expansion may be reactive to toxic, infectious, and neoplastic conditions, or result from clonal selection. Recently, the higher attention to LGL clones led to their detection in many clinical conditions including myeloid neoplasms and bone marrow failures. In these contexts, it is still unclear whether LGL cells actively contribute to anti-stem cell autoimmunity or are only a reaction to dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…This paradox may be speculatively related to the transition of the immune system from pro-inflammatory/pro-apoptotic in early MDS to tumor permissive facilitating leukemic progression in the late stage ( 26 , 42 ). Indeed, somatic mutations may be present not only in the myeloid compartment but also in the immunologic microenvironment, as described for MDS, but also for aplastic anemia and other autoimmune diseases ( 43 45 ). Lymphoid clonality, particularly of CD8+ T-cells and large granular lymphocytes (LGL) in patients with bone marrow failure, may represent both a player in inducing apoptosis of marrow precursors and a result of chronic stimulation via exposure of self-antigens resulting from ineffective erythropoiesis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This paradox may be speculatively related to the transition of the immune system from pro-inflammatory/pro-apoptotic in early MDS to tumor permissive facilitating leukemic progression in the late stage ( 26 , 42 ). Indeed, somatic mutations may be present not only in the myeloid compartment but also in the immunologic microenvironment, as described for MDS, but also for aplastic anemia and other autoimmune diseases ( 43 45 ). Lymphoid clonality, particularly of CD8+ T-cells and large granular lymphocytes (LGL) in patients with bone marrow failure, may represent both a player in inducing apoptosis of marrow precursors and a result of chronic stimulation via exposure of self-antigens resulting from ineffective erythropoiesis.…”
Section: Discussionmentioning
confidence: 97%
“…Lymphoid clonality, particularly of CD8+ T-cells and large granular lymphocytes (LGL) in patients with bone marrow failure, may represent both a player in inducing apoptosis of marrow precursors and a result of chronic stimulation via exposure of self-antigens resulting from ineffective erythropoiesis. In this view, it has been reported that STAT3-mutant LGL clones may facilitate bone marrow failure in a subset of aplastic anemia patients and may be potentially amenable to immunosuppressive treatment ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…1,[4][5][6] Compounding the issue of specificity is that clonal LGL expansions are frequently observed in MNs and frequent STAT3/5B mutations have been reported in MNs with associated LGL expansion. 4,7,8 Rarely, have LGLLs been diagnosed concomitantly in patients with otherwise typical MNs. 9,10 Based on morphology, flow cytometry, and T-cell clonality studies alone, it may be challenging to classify a marrow process with both LGL expansion [11][12][13][14] and morphologic dysplasia 7 (Fig.…”
mentioning
confidence: 99%
“…4,7,8 Rarely, have LGLLs been diagnosed concomitantly in patients with otherwise typical MNs. 9,10 Based on morphology, flow cytometry, and T-cell clonality studies alone, it may be challenging to classify a marrow process with both LGL expansion [11][12][13][14] and morphologic dysplasia 7 (Fig. S1) as an LGLL versus an MN or both.…”
mentioning
confidence: 99%
See 1 more Smart Citation